PENGARUH PROMOSI KESEHATAN TENTANG HIV/AIDS TERHADAP PENGETAHUAN DAN STIGMA MASYARAKAT - lenny simatupang (Jurnal Maternitas Kebidanan, 2019)
HIV and AIDS is a public health problem that requires very serious attention because of the increasing prevalence problem, another problem arises, namely the lack of public knowledge about HIV/AIDS and the stigmatization of HIV/AIDS. Based on this phenomenon, the purpose of the research conducted was to determine the effect of health promotion about HIV/AIDS on community knowledge and stigma in the working area of the Exemplary Health Center. The study design used an experimental design with an experimental design with one group pretest posttest in the working area of the Exemplary Health Center in January - March 2019. The sampling technique was accidental sampling, with a total sample of 81 people. Data analysis includes univariate and bivariate analysis with the Wilcoxon signed rank test. The results obtained by the difference in knowledge and community stigma before and after being given health promotion where the value of p value = <0.05. The conclusion in this study there is a significant influence on HIV / AIDS before dans after being given health promotion. Suggestions that health promotion about HIV / AIDS can be done in health services (health centers, hospitals and clinics) to increase public knowledge and reduce community stigma about HIV/AIDS.